Parasympathetic Nerve Function Status in Female with Rheumatoid Arthritis - Jahan, Kawser; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2013)
Background: Sudden cardiac death in patients with Rheumatoid Arthritis has been attributed to the decreased vagal drive to the heart. Objective: To assess cardiac parasympathetic nerve function status in patients with Rheumatoid Arthritis (RA). Methods: This cross sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January to December 2010. Sixty female RA patients aged 18-50 years were included in the study group. They were enrolled from the Out Patient Department of Rheumatology Wing of the Department of Medicine, BSMMU, Dhaka. For comparison age matched thirty apparently healthy females were also studied as control. To assess parasympathetic nerve function status, all the subjects were examined by three noninvasive cardiovascular reflex tests such as heart rate response to valsalva maneuver (valsalva ratio), heart rate response to deep breathing and heart rate response to standing (30th :15th ratio). For statistical analysis independent sample t test was used. Results: Mean values of valsalva ratio, deep breathing test and 30th :15th ratio were significantly (p<0.001) lower in rheumatoid arthritis patients compared to those of healthy control. Conclusion: From this study it may be concluded that lower cardiac parasympathetic nerve activity characterized the autonomic nerve dysfunction in patients with Rheumatoid Arthritis. DOI: http://dx.doi.org/10.3329/jbsp.v8i1.16643 J Bangladesh Soc Physiol. 2013, June; 8(1): 21-25